Peran Inovasi Produk, Aspek Keuangan, Kompetensi Sumber Daya Manusia Dan Financial Technology Dalam Meningkatkan Kinerja UMKM Kota Mataram - Alvina Damayanti; Herawati Khotmi; Elvina Setiawati (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
The increasingly rapid and rapid development of technology currently offers a lot of convenience for people in doing business globally. This research aims to empirically test the influence of investment knowledge, technological developments, minimum investment capital and investment returns on investment interest of university students in the city of Mataram. This research is associative research with a quantitative approach. The population in this study were active students in universities throughout Mataram City with a sample of 101 students. Data were analyzed using SPSS 23 with classical assumption tests and multiple linear regression. The results of this study indicate that investment knowledge (X1) has no significant effect on investment interest, technological development (X2) has a significant effect on student investment interest, minimum capital (X3) has no significant effect on investment interest and return (X4) has a significant effect on interest. student investment. The results of this research also show that the influence of investment knowledge, technological developments, minimum capital and returns can influence students' investment interest by 55.2%, while the remaining 44.8% is influenced by other variables outside the regression model used in this research